Design de biblioteca: uma abordagem para além dos aspectos estéticos - ALMEIDA, Antonio Júnior Estumano de (2017)
Analyzes design actions in context from the library, as well as, how influences that this space cause in user. In this sense, the overall objective is analyze the importance and the influence esthetic aspect from library in users, be with regard to the visual or psychological aspects caused, with reference to the study of design, at end to find the interferences that environment causes in your audience. The route methodological approach was concentrated in the qualitative analysis reflective on the subject based on a review of literature, with authors who dedicate themselves to study the subject and contextualizing with librarianship. This was done for a bibliographic search in the are of design, where it was intended to show the points of intercession between the design and the library, making the call between one approach and another. As results, far from trying to exhaust the approach to these questions, it is pointed out that these issues are not seen as trivial in the context of the library and that, therefore, they can be better treated for the effective establishment of the bond between user and the unit Of information, making it, the user, have the feeling of being linked to the library. Finally, it is concluded that the environment affects us, causing experience and pleasurable feelings, arousing emotions that make us more apt to learn, and that the factors esthetic has the role important for the user to get, together with other elements, achieve excellence of your pretensions in the library space.